Prinsip-Prinsip Perjanjian Muamalat dalam Hukum Perbankan Syariah di Indonesia - Faisal, Faisal (Universitas Malikussaleh, 2015)
According to the practice of Islamic banking principles, a bank should have muamalat agreement including the principle of deposit or deposits (depository/al-wadi'ah), the principle of profit sharing (profit-sharing), purchase (sale and purchase), leases (operational and financial lease lease), and services (fee-based services). Legal agreement adheres to several principles, including the principle of the freedom of an agreement (the sense of autonomy), the principle of adjustments will, and the principle of trust. In addition, there is also the principle of binding force, the principle of legal equality, the principle of balance, the principle of legal certainty, moral principles, merit principle, and the principle of habit.